Identifikasi dan Pengendalian Risiko Produksi Teh Hitam Orthodoks Pada PT Perkebunan Nusantara VIII: Identification and Risk Control of Orthodox Black Tea Production at PT Perkebunan Nusantara VIII (Case Studi in Afdeling Sinumbra, Rancabali Tea Plantation, West Java) - Aulia, Reza Melvina; Heryanto, Mahra Arari; Rachmawati, Erna; Renaldi, Eddy (JURNAL AGROINDUSTRI HALAL, 2022)
Tea is one of the leading commodities in Indonesia and is mostly produced in West Java, where Afdeling Sinumbra is one of the plantations that produce Orthodox black tea under the auspices of PT Perkebunan Nusantara VIII but has the smallest production contribution. This indicates that there are problems regarding production, and a risk management analysis is needed. The research was carried out from the plantation and processing levels using the House of Risk method consisting of stages 1 and 2. Stage 1 aims to identify risk events and the causes or sources of these risks. While stage 2 aims to formulate appropriate handling strategies to minimize the impact caused by risk sources. This study shows that crop failure is the biggest risk event at the plantation level stemming from delays in handling pests and diseases. The handling strategy that can be done is to increase discipline. Meanwhile, at the processing level, there is a risk that production and grading are not achieved, which stems from the implementation of SOPs that are not appropriate. The handling strategy that can be done is to warm up the engine, repair the engine, and train.